Strategi Komisi Independen Pemilihan dalam Meningkatkan Partisipasi Politik melalui Pendidikan Politik Generasi Muda di Aceh Barat - Roni Hidayat (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Study This review commission strategy independent election regency West Aceh in increase participation political through education politics in generation young West Aceh. Research the use approach qualitative for analyze results research. The informants used source information main there are 3 people. technique data collection with use technique interviews and documentation. For analyze results findings in the field with using triangulation techniques Research results in the field show that the strategy is carried out for to improve participation political through education politics in generation young through the saweu program elbow and saweu campus. Saweu program elbow and sweu campus This carried out in form activity workshop Activity this is very effective in give understanding politics in generation young and able increase participation they in event politics in the district West Aceh. The conclusion is that many strategies can be used in increase participation political public However for generation young the most effective strategy in increase participation political through education political namely the sawe program elbow and sawe campus